Debatten i debatten - Jenny Eklöf (Lychnos)
In the late 1970s, the media debate about recombinant DNA technology was Sweden’s first, but far from last, controversy about the risks and possibilities of genetic engineering. Based on the concept of knowledge cartographies, this study highlights how the main actors in the debate tried to make sense of what gene technology entailed, but also, and more importantly, how knowledge about the technology and its consequences should be communicated and disseminated in society. The article shows that the combination of a relatively unanimous research community with the absence of an organized and engaged public meant that the communicative line of conflict mainly came to stand between researchers on one side and the mass media and individual politicians on the other. Here, long-established trust in experts stood against a new approach in which the research community was held democratically and morally accountable. The whole debate can be understood as being placed in a transitional period in which the previously dominating authoritative knowledge cartography began to make room for a burgeoning public sphere cartography. The debate was also colored by its contemporary context; by other ongoing science-related controversies, such as that of nuclear power, and not least by the emergence of new journalistic ideals and broader public discussions about academic freedom and scientists’ communicative obligations.